Effects of mindfulness-based music listening on conflict control in young adults with insomnia disorder: behavioral and event-related potential evidence - Shi, Huijuan; Liu, Yi; Liu, Yong; Zheng, Maoping; Liu, Xiaolin (Frontiers in Psychology, 2024)
Introduction Insomnia Disorder (ID) has become the second most prevalent mental disorder, with significant negative effects on daytime cognitive functions. Previous studies suggested that mindfulness-based music listening (MBML) can effectively improve conflict control and attentional processing in healthy adults. However, the behavioral and neurophysiological characteristics of MBML in young adults with ID remain unclear. Methods To explore the behavioral and neurophysiological characteristics of MBML in regulating negative emotions among young Chinese adults with ID, 60 young adults with ID were asked to complete an emotion-word Stroop task under three mood states while recording event-related potentials (ERPs). Results Task and questionnaire results showed that (1) negative emotion induced by the negative simulated video significantly suppressed the attentional processing of emotional faces and words in the conflict control task among young people with ID, (2) MBML reduced cognitive and physical arousal levels, enhanced positive mood, and improved attentional control abilities in young adults with ID. The ERP results showed that a greater N3 effect and the smaller P3 and late positive component (LPC) effects reflected that MBML effectively regulated negative emotions induced by the negative simulated video and attentional processing abilities for conflict control in young adults with ID. Discussion Maintaining mindfulness while listening to music may enhance positive emotional experiences and improve cognitive ability, and exhibit larger N3 effects and smaller P3 and LPC effects in the electrophysiology mechanism, with a reduction in the hyperarousal level in young adults with insomnia disorders.